Utilization of Dried Banana Leaf Waste and Addition of Molasses as a Growing Media for White Oyster Mushroom Growth (Pleurotus Ostreatus) - Yahya, Muhammad; Rasjid, Yusniar; Sunarti, Lilis (PT ARRUS Intelektual Indonesia, 2023)
This type of research is a pure experimental type of research and uses a quantitative experimental approach, which aims to: (1) find out whether there is an effect of dry banana leaf waste media and the addition of molasses on the growth of white oyster mushrooms (Pleurotus ostreatus), (2) find out how many treatments dry banana leaf waste media and the addition of molasses which gave the best results for the growth of white oyster mushrooms (Pleurotus ostreatus). This research was structured in a Completely Randomized Design (CRD) with a single factor consisting of 7 treatments and carried out 4 times. Thus, there are a total of 28 baglogs/experimental units. The data analysis technique used is an analysis of variance (ANOVA) with a further test using the Least Significant Difference (BNT). The results of the research showed that the planting medium of dried banana leaf waste and the addition of molasses had a real effect on the initial time of mycelium growth (HSI), and the time to pour the mycelium (full colony) (HSI), and had no real effect on the width of the cap (cm), length ( cm), and wet fruit body weight (gr) of white oyster mushroom (Pleurotus ostreatus). The best treatment results on dry banana leaf waste planting media and the addition of molasses to the fastest initial growth time of the mycelium were in treatment (D2) (4.25 HSI), and the fastest time of heating the mycelium (full colony) was in treatment D0 (29 DAS). Meanwhile, D5 was the best treatment for hood